Rahasia Sumpah Allah dalam Al-Quran - Zulihafnani Zulihafnani (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Al-Qur‟an is addressed to all mankind, who gave different reaction in accepting and believing it. Therefore, oaths in Qur-an are meant to remove doubt and misunderstanding and to make argument and confirm news. This is in accordance with the nature of Arab community who used to oath. Historically, the revelation could not be separated from the tradition of Arab community. Also the wisdom of the oath, it could not be detached from the condition of Arab at the time, which, historically, an oath was a hereditary tradition. They made an oath as a mean to affirm argument, assert command, or remove doubt from the opponent.